Conservation Objectives and Policy Trade-offs - Smale, Melinda; King, Amanda (International Food Policy Research Institute, 2005)
The decision to define or measure diversity in a certain way for conservation or development policy can have unforeseen impacts on other types of diversity. For example, efforts to promote the diversity of one crop in a multicrop system can lead to a loss or decline of diversity in another crop.